Eksplorasi Tingkat Stres dan Strategi Coping Mahasiswa Kedokteran Tingkat Akhir yang Mengalami Stagnasi dalam Penyusunan Skripsi: Studi Kualitatif di FK Universitas Tanjungpura: Penelitian - Lo, Anggraini Millennia; Yuniarni, Desni; Armyanti, Ita (Cermin Dunia Kedokteran, 2026)
Introduction: Final-year medical students often face significant academic pressure during the thesis-writing process, which can lead to stress and stagnation in academic progress. This stagnation reflects the tension between academic demands, internal pressures, and environmental factors that affect students’ psychological balance. Unmanaged stress may cause emotional, physical, and cognitive strain, as well as the use of maladaptive coping strategies that hinder academic productivity. This study aims to explore the levels of stress, stress responses, the nature of stress, and coping strategies among final-year medical students experiencing stagnation in thesis completion. Method: This research employed a qualitative, phenomenological approach to understand the subjective experiences and meanings of academic stress among medical students. Participants were selected through purposive sampling, comprising 10 final-year medical students who met the criteria for thesis stagnation. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis to identify patterns in stress experiences and coping mechanisms. Results: The findings indicate that most participants experienced moderate to severe stress, reflected in emotional responses (anxiety, frustration, and loss of motivation), physical symptoms (fatigue, sleep disturbance, and psychosomatic complaints), and cognitive impacts (difficulty concentrating, overthinking, and procrastination). The nature of stress varied between positive stress (eustress), which enhanced motivation, and negative stress (distress), which hindered progress. Coping strategies were classified as adaptive (seeking social support, prayer, and time management) and maladaptive (avoidance, withdrawal, and delay). Institutional barriers, including bureaucratic constraints, academic hierarchy, and limited psychosocial support, were found to exacerbate thesis stagnation. Conclusion: High stress levels among final-year medical students are associated with complex stress responses and a tendency toward maladaptive coping when academic and emotional support is lacking. Therefore, medical institutions need to implement time and stress management training, psychosocial mentoring, and an early academic warning system to foster a supportive learning environment and prevent stress from escalating during the thesis-writing process.